Leveraging wildfire to augment forest management and amplify forest resilience - Kristen L. Shive; Clarke A. Knight; Zachary L. Steel; Charlotte K. Stanley; Kristen N. Wilson (Ecosphere)
Abstract Successive catastrophic wildfire seasons in western North America have escalated the urgency around reducing fire risk to communities and ecosystems. In historically frequent‐fire forests, fuel buildup as a result of fire exclusion is contributing to increased fire severity. The probability of high‐severity fire can be reduced by active forest management that reduces fuels, prompting federal and state agencies to commit significant resources to increase the pace and scale of fuel reduction treatments. However, lower severity areas of wildfires also have the potential to act as “treatments,” and even catastrophic fires with large areas of high severity can still have substantial areas of lower severity fire that may be improving forest conditions locally. We quantified active management and wildfire severity across yellow pine and mixed conifer (YPMC) forests in the Sierra Nevada of California over a 22‐year period (2001–2022). We did not detect increases in the area treated through time, but the area of beneficial wildfire (low to moderate severity) increased substantially, exceeding active treatment area in 8 of 22 years. Overall, beneficial wildfire treated ~17% more area than all treatments combined, and roughly four times more area than fire‐related treatments alone. We then used disturbance history to evaluate resistance to high‐severity wildfire and forest loss across the YPMC range. Of the 2.3 million ha YPMC of forests in 2001, 20% lost mature forests due to high‐severity fire by 2022, which is nearly half of all YPMC area burned. Most of the landscape (47%) remains at risk of high‐severity fire because it had no restorative disturbances, but 33% of the study area has some level of resistance to high‐severity wildfire. In these areas, resistance will need to be enhanced and maintained over time via active management or managed wildfire, but these treatment needs will likely outpace capacity even under optimistic implementation scenarios. Given limited resources for implementing active management and the likelihood of a more fiery future, incorporating beneficial wildfire into landscape‐level treatment planning has the potential to amplify the impact of active management treatments.